2020
DOI: 10.1002/jbm.a.36932
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactor cultivation condition for engineered bone tissue: Effect of various bioreactor designs on extra cellular matrix synthesis

Abstract: Dynamic-based systems are bio-designed in order to mimic the micro-environments of the bone tissue. There is limited direct comparison between perfusion and perfusion-rotation forces in designing a bioreactor. Hence, in current study, we aimed to compare given bioreactors for bone regeneration. Two types of bioreactors including rotating & perfusion and perfusion bioreactors were designed. Mesenchymal stem cells derived from buccal fat pad were loaded on a gelatin/ β-Tricalcium phosphate scaffold. Cell-scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…To overcome the diffusion limitation, various perfusion bioreactors have been developed over the years 6,10–18 . An example of a perfusion bioreactor is hollow fibre membrane bioreactors (HFMBs) 5,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the diffusion limitation, various perfusion bioreactors have been developed over the years 6,10–18 . An example of a perfusion bioreactor is hollow fibre membrane bioreactors (HFMBs) 5,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bioreactor-incubated cell-seeded scaffolds were characterized by greater amounts of ECM proteins including glycosaminoglycans and collagen [88]. In another study, it was proven that cells cultured in a rotating/perfusion bioreactor showed a significantly higher expression of osteogenesisrelated genes (RUNX2, ALP, OC, and COL 1) compared to the cells cultured in the static condition as well as in the perfusion bioreactor [89]. Thus, those observations led to a hypothesis that rotating bioreactors with continuous medium perfusion are an effective approach in BTE and may be used not only as a device for research but also as a tool for the production of living bone tissue graft.…”
Section: Rotating Bioreactorsmentioning
confidence: 99%
“…Rotating bioreactors offer major advantages over spinner flasks since they also control the supply of oxygen and exert low fluid shear stress and turbulence ( Kimelman-Bleich et al, 2011 ; Weszl et al, 2012 ; Song et al, 2013 ; Shekaran et al, 2015 ; Song et al, 2016a ; Demir et al, 2018 ; Westman et al, 2019 ; Daulbayev et al, 2020 ; Nokhbatolfoghahaei et al, 2020a ; Nokhbatolfoghahaei et al, 2020b ; Nokhbatolfoghahaei et al, 2020c ). The most common rotating wall bioreactor is formed by two concentric cylinders: 1) the outer one is a culture chamber and accommodates the cellularized scaffold, submerged in culture medium, while 2) the inner cylinder is static and permits gas exchange ( Figure 1B ).…”
Section: In Vitro Approaches To Mimic Interstitial Fluid Flow: An Overview Of Biomechanical Cluesmentioning
confidence: 99%